PREVENTIVE MEDICINE AS AN IMPORTANT COMPONENT OF THE ACTIVITY OF PRIMARY CARE INSTITUTIONS - Домитращук, Иванна; Мельничук, Лариса (SWorldJournal, 2020)
Health care reform in Ukraine is focused on the development of primary health care based on family medicine. The focus on family medicine should make up for gaps in the prevention work of health facilities. An indicator of the effectiveness of preventive